2015
DOI: 10.1007/s40620-015-0173-5
|View full text |Cite
|
Sign up to set email alerts
|

Eculizumab in pregnancy-associated atypical hemolytic uremic syndrome: insights for optimizing management

Abstract: Pregnancy-associated atypical hemolytic uremic syndrome is a systemic disease associated with high morbidity and mortality rates, caused by dysregulation of the alternative complement pathway, leading to uncontrolled complement activation resulting in thrombotic microangiopathy. This condition can be effectively treated by anti-C5 therapy, which controls complement activation. Treatment can be safely discontinued after complete remission and resolution of the precipitating cause, especially in patients with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 19 publications
0
28
0
1
Order By: Relevance
“…Exposure to eculizumab during pregnancy was associated with a comparable rate of live births and a low rate of maternal complications in contrast to reports of elevated maternal mortality rates observed among patients with PNH not receiving eculizumab (Kelly et al , ). In aHUS, use of eculizumab in pregnancy and post‐partum is associated with good maternal and fetal outcomes, including normalization of haematological outcomes and renal function (Ardissino et al , ; Delmas et al , ; Zschiedrich et al , ; Canigral et al , ; Mussoni et al , ; De Sousa Amorim et al , ; Demir et al , ; Saad et al , ; Servais et al , ; Tsai & Kuo, ; Andries et al , ; Bruel et al , ; Chua et al , ; Gately et al , ). The rate of congenital malformation reported in neonates born to mothers treated with eculizumab lies within the range of that reported in the general population (UK Teratology Information Service, ).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to eculizumab during pregnancy was associated with a comparable rate of live births and a low rate of maternal complications in contrast to reports of elevated maternal mortality rates observed among patients with PNH not receiving eculizumab (Kelly et al , ). In aHUS, use of eculizumab in pregnancy and post‐partum is associated with good maternal and fetal outcomes, including normalization of haematological outcomes and renal function (Ardissino et al , ; Delmas et al , ; Zschiedrich et al , ; Canigral et al , ; Mussoni et al , ; De Sousa Amorim et al , ; Demir et al , ; Saad et al , ; Servais et al , ; Tsai & Kuo, ; Andries et al , ; Bruel et al , ; Chua et al , ; Gately et al , ). The rate of congenital malformation reported in neonates born to mothers treated with eculizumab lies within the range of that reported in the general population (UK Teratology Information Service, ).…”
Section: Discussionmentioning
confidence: 99%
“…After the development of complement regulation mechanisms and aHUS pathogenesis, eculizumab has been widely used as a first-line treatment in aHUS. Recent studies showed that early diagnosis and rapid use of eculizumab in first-line treatment improve outcomes [7, 8, 9]. We diagnosed aHUS due to TMA, acute kidney injury, and thrombocytopenia with normal ADAMTS level and thrombi in arteriolar and glomerular capillary lumina in 3 days; however, we could not use eculizumab in first-line treatment because of our government health insurance restrictions due to unlabelled usage of eculizumab in aHUS treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Multiple studies have described the use of plasma exchange therapy immediately after diagnosis of aHUS until hematologic parameters stabilize, followed by eculizumab therapy with good overall outcomes and renal recovery. 2,7 It is thought that plasma exchange significantly increases survival rates by transiently correcting laboratory abnormalities, but ultimately complement inhibitors are necessary to improve renal recovery by inhibiting the underlying complement dysregulation. 7 Before the advent of eculizumab, plasma therapy was considered the mainstay of treatment with good survival rates but high rates of morbidity associated with end stage renal disease.…”
Section: Proceedings In Obstetrics and Gynecologymentioning
confidence: 99%
“…2,7 It is thought that plasma exchange significantly increases survival rates by transiently correcting laboratory abnormalities, but ultimately complement inhibitors are necessary to improve renal recovery by inhibiting the underlying complement dysregulation. 7 Before the advent of eculizumab, plasma therapy was considered the mainstay of treatment with good survival rates but high rates of morbidity associated with end stage renal disease. 1 Eculizumab is a humanized monoclonal antibody that arrests complement activation and progression of TMA by binding with high affinity to human C5 complement protein and preventing pro-inflammatory complement formation.…”
Section: Proceedings In Obstetrics and Gynecologymentioning
confidence: 99%